2007
DOI: 10.1007/s10683-006-9136-y
|View full text |Cite
|
Sign up to set email alerts
|

Stability of risk preference parameter estimates within the Becker-DeGroot-Marschak procedure

Abstract: This paper reports new data from both selling and buying versions of the Becker-DeGroot-Marschak (BDM) procedure. First, when using the selling version of BDM, the cross-sectional mean of CRRA risk preference parameter estimates shifts from a value consistent with “as if†risk-seeking behavior in the early baseline to a value closer to “as if†risk neutrality in the late baseline. Second, when using the buying version of BDM, the cross-sectional mean of CRRA risk preference parameter estimates does not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
4
10
0
1
Order By: Relevance
“…A closer look at the individual data reveals that the variance in individual decisions across lotteries is rather high. This finding is consistent with that of, e.g., James (2007), who estimates risk preference parameters on a time series of data from the Becker-DeGroot-Marschak mechanism, breaking the series into four different regimes. According to his estimates, most subjects switch from risk aversion to risk seeking behavior (or vice versa) in moving from one treatment regime to the other.…”
Section: Risk Attitude Estimatessupporting
confidence: 91%
“…A closer look at the individual data reveals that the variance in individual decisions across lotteries is rather high. This finding is consistent with that of, e.g., James (2007), who estimates risk preference parameters on a time series of data from the Becker-DeGroot-Marschak mechanism, breaking the series into four different regimes. According to his estimates, most subjects switch from risk aversion to risk seeking behavior (or vice versa) in moving from one treatment regime to the other.…”
Section: Risk Attitude Estimatessupporting
confidence: 91%
“…Our results show that typical non-expected utility patterns as modeled by prospect theory may not provide an appropriate description of choice behavior if time pressure becomes important. We have shown that recently developed models of 9 A similar effect has been found in Issac and James (2000) and James (2007) in comparisons between risk attitude elicitation procedures. In the two studies the subjects who are most risk averse under one elicitation procedure are most risk seeking under the other procedure, suggesting that differences in elicited risk attitudes depend on differences in the susceptibility towards the specific framing of the procedure.…”
Section: Resultssupporting
confidence: 74%
“…Our finding of evidence for models with buyer-seller differences in response bias even under conditions of incentive compatibility suggests that lack of understanding of the BDM procedure or implicit, automatic factors, which are less under the decision-maker's control, play at least some role. Although the BDM procedure is a commonly used method for encouraging people to state their actual subjective valuations, there is some evidence that participants do not always fully understand it (e.g., Cason & Plott, 2014;James, 2007;Safra, Segal, & Spivak, 1990). Despite due efforts to clearly explain the procedure to participants, we cannot rule out that in Study 2 some participants did not completely understand it.…”
Section: The Role Of Response Bias In the Endowment Effectmentioning
confidence: 93%
“…The arguably most prominent account of this type is loss aversion (Kahneman et al, 1990), which posits that buyers and sellers differ in their sensitivity to the magnitude of an object's potential consequences (see below for details). Further, there is evidence in valuations of risky options that buyers and sellers differ in probability weighting (e.g., Brenner, Griffin, & Koehler, 2012), and some authors have highlighted the role of strategic misrepresentation (e.g., Heifetz & Segev, 2004;Isoni, Loomes, & Sugden, 2011;Plott & Zeiler, 2005, 2007. Finally, Yechiam and Hochman (2013a) have recently proposed a loss-attention account, according to which buyers and sellers may differ in the amount of attention they invest in a task.…”
Section: Abstract Computational Modeling Endowment Effect Risky Dmentioning
confidence: 99%